Prolonged use of nitrazepam for epilepsy in children with tuberous sclerosis. Issue 6497 (14th September 1985) - Dennis, J; Hunt, A
Abstract : A case note study of 90 children with tuberous sclerosis showed that 56 had taken nitrazepam for seizures for from one month to 13 years. In 38 children nitrazepam was withdrawn but only two had immediate major seizures. Given that sleepiness, deterioration in motor skills, or ataxia seems to be associated in some children with treatment with nitrazepam, doctors may wish to review their long term prescriptions of this drug in children with tuberous sclerosis.